Capaian Penerapan Sistem Informasi Pemerintah Daerah Terhadap Pelaporan Keuangan Di Kabupaten Jayawijaya - Natasya Herlin Lauw, Ria; Salle, Agustinus; R. Muslimin, Ulfah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This research aims to determine the criteria achieved in implementing SIPD in Jayawijaya Regency and what obstacles were faced during the implementation process. This research uses a qualitative method with a descriptive approach. The data in this research was obtained from 7 informants. The data collection techniques are observation, interviews, literature study and documentation. The analysis tool is qualitative descriptive. The interview results were processed using Voyant Tools to be able to see what words appeared most often during the interview. The results of this research show that the criteria based on policy implementation proposed by Van Meter and Van Horn have been implemented although there are still several obstacles. The implementation achievements based on the effectiveness theory put forward by Duncan are quite good, although in implementation there are several obstacles such as the network and the SIPD menu which are not yet perfect. The inhibiting factors found in the research are that the quality of human resources needs to be improved, and network errors still occur.